Hybrid Heuristics for The Dial-A-Ride Problem with Transfer and Synchronization in Central Hub - Said Hammouda; Ali Lemouari; Mokhtar Taffar (Statistics, Optimization & Information Computing, 2022)
This paper deals with the dial-a-ride problem with transfer, where a set of customer demands are divided into two different regions, such as the pickup and delivery nodes must not be in the same region for a given request. Two vehicles are needed to meet customer demand which implies a synchronization process between vehicles in the transfer point called a central hub. In this paper, we provide a solution method based on an adaptive large neighborhood search algorithm (ALNS), to stretch the neighborhood of a solution, which gives the best search space exploration. Effificient constructions methods are proposed to repair a destroyed solution, giving a large possibility case. An intensifification mechanism is ensured by blending the proposed ALNS with TS and SA algorithms. Implemented algorithms outperform all comparison methods such as memetic algorithms regardless of the quality solution and the run-time for all existing benchmarks sets.